The Importance of Income Inequality for Human Capital Investment in the Period 1970–2012 - Bartak, Jakub; Jabłoński, Łukasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The paper presents an empirical analysis of the importance of income inequality for human capital investment in various countries of the World between 1970 and 2012. The analysis was conducted with the estimation of regression parameters, with quantitative and qualitative measures of human capital investment as independent variables. With the analysis based on panel data, it was possible to control the calculations for individual countries, time and random effects. That is the contribution to the debate over the relations between income inequality and quantitative investment in human capital. Our calculations show a negative relationship between income inequality and quantitative measures of human capital investment. This negative relationship is resistant to the model’s specifications. However, the calculation results do not allow us to draw conclusions about the relationships between income inequality and a qualitative measure of human capital investment.